Utilization of Solar Panels as an Energy Source in the Egg Hatcher Temperature Control Automation System: Utilization of Solar Panels as an Energy Source in the Egg Hatcher Temperature Control Automation System - Miduk Purba; Angelia Maharani Purba (Jurnal Mantik, 2020)
The purpose of this study was to increase the production of chicks through egg incubators by using solar panels as a backup source of energy in controlling the temperature and humidity of the air. Manufacture of egg incubators through design with a capacity of 20 eggs. Hatching room temperature during egg incubation in the first 18 days is 37?C - 38?C, while the hatching period from day 19 to day 21 is 38?C - 39?C. Humidity is maintained in the first 18 days 50% - 55% RH and in the hatching period on the 19th- 21st day air humidity 55% - 60%RH. From the results of tests and observations, the temperature and humidity values ??are in accordance with the desired 38°C - 39°C and relatively stable humidity that is 50% - 60%RH. This tool can be used as an egg incubator without worrying about the electricity flow is interrupted.